92 Adoptive transfer of immature myeloid cells lacking NF-κB p50 (p50-IMC) slows high-risk neuroblastoma tumor growth. (10th December 2020) - Cui, Cheng; Barberi, Theresa; Suresh, Rahul; Zimmerlin, Ludovic; Zambidis, Elias; Friedman, Alan
Abstract : Background: High-risk neuroblastomas, including those with MYCN gene amplification, harbor abundant myeloid cells that suppress anti-tumor immunity and favor tumor growth. Macrophages lacking the inhibitory NF-κB p50 subunit adopt an M1-polarized, T-cell-activating phenotype. Multiple cancers grow slower in mice lacking p50, and colon cancer grows slower in mice lacking p50 specifically in myeloid cells. Methods: Tumor growth was monitored in mice inoculated subcutaneously with 9464D cells. To generate p50-IMC from p50 -/- mice, marrow cells were lineage-depleted and then expanded in media with SCF, FL, and TPO, followed by transfer to M-CSF for one day. To generate p50-IMC from wild-type mice, marrow cells were nucleofected with a p50 sgRNA:Cas9 complex, followed by expansion in serum-free media. Mice received 5-fluorouracil on day 27, followed five days later by three doses of 1E7 p50-IMC via tail vein every three to four days. PD-1 antibody was administered twice weekly for four doses, starting on day 32. Azacytidine was administered 5 days per week alternating with ITF-2357 5 days per week, again starting on day 32. CD4 and CD8 antibody was given twice weekly starting on day 21. Tumor T cells were analyzed by flow cytometry. Results: We have now found that murine 9464D neuroblastoma cells, expressing high levels of exogenous human MYCN, also grow slower in syngeneic C57BL/6 (B6) p50(f/f);Lys-Cre mice, lacking p50 in macrophages and neutrophils, compared with p50(f/f) littermates. Slowed tumor growth in p50(f/f);Lys-Cre mice was associated with increased total and activated tumor CD4 + and CD8 + T cells, and depletion of both CD4 + and CD8 + T cells accelerated tumor growth. PD-1 checkpoint blockade or DNA methyltransferase and histone deacetylase inhibition further slowed tumor growth in p50(f/f);Lys-Cre mice. In addition, adoptive transfer of p50-IMC, generated either from the bone marrow of p50 -/- B6 mice or via nucleofection of a p50 sgRNA:Cas9 complex into wild-type B6 hematopoietic progenitors, also slowed neuroblastoma tumor growth, following a dose of myelo-depleting 5-fluorouracil. Conclusions: These findings using a neuroblastoma model further validate the utility of targeting myeloid NF-κB p50 as an immunotherapy strategy for cancer therapy and demonstrate activity of p50-IMC generated by gene editing of syngeneic marrow cells, a cell product relevant to clinical translation. We have also developed means to efficiently gene edit p50 in human marrow CD34 cells, and have demonstrated the feasibility of generating p50-IMC from human induced pluripotent stem cells. We are currently evaluating the efficacy of these gene-edited human cells against human neuroblastoma in immune-deficient mice.